2022
DOI: 10.1039/d2cp03713k
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent catalytic hydrogen productionviamethane decomposition and aromatization at a low-temperature using Co, Ni, Cu, Mo, and Ru nanometals

Abstract: Catalytic methane decomposition to hydrogen and aromatization are inevitable for development of natural gas usage. Metal catalysts have been developed to achieve highly efficient methane decomposition and aromatization under 1000...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Extensive research efforts have shown that in most of the cases, the catalyst gets decomposed to its individual oxides in the reaction atmosphere, thus losing their parent oxide phases. 11,25,28,33,35,37,[42][43][44] The most astonishing feature of this very double perovskite oxide catalyst is the regeneration of the pristine phase out of the decomposed compositions by heating at a temperature significantly lower than the initial synthesis temperature. Actually, the regeneration of double perovskite can take place at 600 1C or 700 1C for 3 h heating, whereas the synthesis temperature was 800 1C, as mentioned earlier.…”
Section: Powder Xrd Analyses Of the As-prepared Aged And Regenerated ...mentioning
confidence: 99%
“…Extensive research efforts have shown that in most of the cases, the catalyst gets decomposed to its individual oxides in the reaction atmosphere, thus losing their parent oxide phases. 11,25,28,33,35,37,[42][43][44] The most astonishing feature of this very double perovskite oxide catalyst is the regeneration of the pristine phase out of the decomposed compositions by heating at a temperature significantly lower than the initial synthesis temperature. Actually, the regeneration of double perovskite can take place at 600 1C or 700 1C for 3 h heating, whereas the synthesis temperature was 800 1C, as mentioned earlier.…”
Section: Powder Xrd Analyses Of the As-prepared Aged And Regenerated ...mentioning
confidence: 99%
“…Fundamental studies have elucidated the mechanisms of methane activation and transformation on nanoscale catalysts, providing insights into key factors governing catalytic performance [29,30]. Experimental and computational approaches have been employed to characterize the structureactivity relationships of nanocatalysts and identify the optimal catalyst formulations for enhanced methane conversion efficiency and selectivity [31,32]. Moreover, advances in in situ and operando characterization techniques have enabled the real-time monitoring of catalyst dynamics under reaction conditions, facilitating the rational design of nanocatalysts with improved stability and performance [33].…”
Section: Methane Activation Strategiesmentioning
confidence: 99%